2022
DOI: 10.1002/ptr.7438
|View full text |Cite
|
Sign up to set email alerts
|

United States Pharmacopeia comprehensive safety review of Styphnolobium japonicum flower and flower bud

Abstract: The dried flower and flower bud of Styphnolobium japonicum (L.) Schott (Japanese Sophora flower and Japanese Sophora flower bud, respectively) have long been used as herbal medicines in Asia. Today, they are marketed as dietary supplements in the United States for their anti‐oxidative properties and as a source of flavonoids, including rutin and quercetin. This review focused on the safety of S. japonicum flower and flower bud as dietary supplement ingredients. No serious adverse events or toxicity were report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The flowers and flower buds of S. japonicum have been recognized for their rich flavonoid content and medicinal properties in Asia, particularly for their antioxidative properties [ 31 ]. These attributes, coupled with the diverse secondary metabolites present, have positioned S. japonicum flowers as economically significant crops in various regions of China [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flowers and flower buds of S. japonicum have been recognized for their rich flavonoid content and medicinal properties in Asia, particularly for their antioxidative properties [ 31 ]. These attributes, coupled with the diverse secondary metabolites present, have positioned S. japonicum flowers as economically significant crops in various regions of China [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to different flowering stages, it can be divided into Huairui (mature flower) and Huaimi (flower bud). Huaimi is a rich and important source of rutin and is easy to extract [14,15,20]. Modern pharmacological studies have shown that the active ingredients of Huaimi extract have a wide range of pharmacological effects, such as antibacterial, anti-inflammatory, antioxidant, antiviral, and antitumor [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Phenylpropanoids play an important role in adaptation, including flavonoids and lignins, which are used in the development, growth, and reproduction of plants [20,21].…”
Section: Phenylpropanoid Biosynthesis During Development Of Huaihuamentioning
confidence: 99%
“…It contains large amounts of flavonoids such as rutin, quercetin, and kaempferol (Pi et al, 2018), which have anti-inflammatory, antibacterial, anti-cancer, hemostatic, and antihypertensive properties (Gong et al, 2021). Furthermore, FS was used as a potential natural antioxidant in Chinese sausages and marketed as a dietary supplement in the United States due to its anti-oxidative properties (Fan et al, 2020;Tang et al, 2019;Madden et al, 2022).…”
Section: Introductionmentioning
confidence: 99%